Malnutrition coding shortfalls in Australian and New Zealand hospitals. Issue 1 (24th March 2014) - Agarwal, Ekta; Ferguson, Maree; Banks, Merrilyn; Bauer, Judith; Capra, Sandra; Isenring, Elisabeth
Abstract Aim The International Classification of Diseases, version 10, Australian modification (ICD‐10‐AM) is used to classify diseases in hospital patients in Australia and New Zealand. ICD‐10‐AM defines malnutrition as '[body mass index] BMI <18.5 kg/m2 or unintentional weight loss of ≥5% with evidence of suboptimal intake resulting in subcutaneous fat loss and/or muscle wasting'. The Australasian Nutrition Care Day Survey (ANCDS) is the most comprehensive survey to evaluate malnutrition prevalence in acute care patients from Australian and New Zealand hospitals. This study determined if malnourished participants were assigned malnutrition‐related codes according to ICD‐10‐AM. Methods The ANCDS recruited acute care patients from 56 hospitals. Hospital‐based dietitians evaluated participants' nutritional status using BMI and Subjective Global Assessment (SGA). In keeping with the ICD‐10‐AM definition, malnutrition was defined as BMI <18.5 kg/m2, SGA‐B (moderately malnourished) or SGA‐C (severely malnourished). After 3 months, in this prospective cohort study, staff members from each hospital's health information/medical records department provided coding results for malnourished participants. Results Malnutrition was prevalent in 30% (n = 869) of the cohort (n = 2976) and a significantly small number of malnourished patients were coded for malnutrition (n = 162, 19%, P < 0.001). In 21 hospitals, none of the malnourished participants were coded. Conclusions This is the largest study to provide a snapshot of malnutrition coding in Australian and New Zealand hospitals. Findings highlight gaps in malnutrition documentation and/or subsequent coding, which could potentially result in significant loss of casemix‐related revenue for hospitals. Dietitians must lead the way in developing structured processes for malnutrition identification, documentation and coding.